The Value of the Corporate Governance Canon on Chinese Companies - Bryane Michael; Say-Hak Goo (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
China has yet to import the corporate governance “canon” (generally accepted rules as promoting share holder value as well as minority shareholder and other stakeholders' rights) into its Code of Corporate Governance. What effect would Chinese companies' simply adopting such a canon – as defined by Hong Kong or other foreign corporate governance practices – have on their share prices? We look at Mainland Chinese companies listed in Hong Kong, looking at the way their share prices react to economic fluctuations when they have better or worse corporate governance practices. Using a differences-of-differences methodology, that such share prices could/would increase by around 7% – increasing profits by about 330 billion. Yet, a significant part of the distribution of these companies loose money in the short-run. These results provide yet another confirmation that adopting the corporate governance canon can profit companies' investors, but not all of them.
Keywords: G34; N25; M14; 330; Chinese corporate governance; post-crisis economics; differences-in-differences; Hong Kong